Tindak pidana terhadap nyawa dan tubuh : pemberantasan dan prevensinya : dilengkapi yurisprudensi Mahkamah Agung RI dan pembahasan - Marpaung, Leden; Indonesia. Mahkamah agung (Jakarta : Sinar Grafika, 2000)
Murder and other offenses against the person; comments on court decisions of the Indonesian Supreme Court
Includes bibliographical references (p. 263-264)
Keywords: Offenses against the person -- Indonesia; Murder -- Indonesia